2015
DOI: 10.1111/1750-3841.12884
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Low Sodium Salts Mix for Shoestring Potatoes

Abstract: Several studies have shown the close relationship between the sodium consumption and health problems such as hypertension and cardiovascular disease. Thus, the demand for products with reduced sodium content, but with sensory quality, is increasing every day. In this context, this study aimed to optimize a low sodium salts mix using sodium chloride, potassium chloride, and monosodium glutamate to the development of shoestring potatoes with low sodium content and high sensory quality, through mixture design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Considering that the sodium chloride added and considering it have approximately 400 mg of sodium/g of sodium chloride (Pereira et al, 2015), the control sample has 520 mg/Na and the formulations with a 50 or 75 per cent NaCl reduction have 260 and 130 mg/Na, respectively.…”
Section: Experimental Design and Beef Burger Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the sodium chloride added and considering it have approximately 400 mg of sodium/g of sodium chloride (Pereira et al, 2015), the control sample has 520 mg/Na and the formulations with a 50 or 75 per cent NaCl reduction have 260 and 130 mg/Na, respectively.…”
Section: Experimental Design and Beef Burger Processingmentioning
confidence: 99%
“…Therefore, the World Health Organisation (2007) defined as "safe" the intake of 5 g of NaCl per day because this quantity satisfies the basic requirements of the human body (200-500 mg of sodium a day) (Bannwart et al, 2014) without compromising health. Nonetheless, there is still excessive intake of NaCl in the population (Pereira et al, 2015) owing to the ingestion of highly processed food products, which contribute up to 75 per cent of the total sodium intake. Meat products, for example, can contribute up to 18 per cent of this amount (Tobin et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Khetra et al (2016) showed that it is possible to considerably reduce sodium amount in Cheddar cheese by using a combination of a salt replacer, HVP and adenosine-5'-monophosphate, which also in case of cheese reduced bitterness. Several studies found that one of best combinations for salt reduction is a mixture of NaCl, KCl and MSG (Pereira et al, 2015;Rodrigues et al, 2016). The optimum salt content for chips and snacks in the snack sector has been observed at approximately 1.6% NaCl, research about salt level reduction in shoestring potatoes has shown that it is possible to maintain the same level of salt perception and similar sensory acceptability by using a mix of NaCl (30%), MSG (30%) and KCl (40%) to provide salt taste, where optimal formulation in product would be 0.48% of sodium chloride, 0.92% of potassium chloride, and 0.43% of monosodium glutamate, which accordingly would equivalent in salty taste to 1.6% NaCl (Pereira et al, 2015).…”
Section: Salt Replacers and Flavour Enhancersmentioning
confidence: 99%
“…The addition of salt during cooking and processing enhances the palatability of consumed food. In this context, salt is a flavor enhancer that gives a salty taste upon addition to food (Dotsch et al, 2009; Pereira et al, 2015). Salt content in food is related to food preference among children (Bouhlal, Chabanet, Issanchou, & Nicklaus, 2013).…”
Section: Introductionmentioning
confidence: 99%